Parental pain is not associated with pain in the child: a population based study. Issue 9 (12th August 2004) - Jones, G T; Silman, A J; Macfarlane, G J
Abstract : Background: Child pain is associated with adverse psychosocial factors. Some studies have shown an association between children's and parental pain. Children may "learn" pain behaviour from their parents. Objectives: To examine whether an association exists between parent and child pain, and, if so, whether this relationship persists after adjusting for psychosocial difficulties in the child. Methods: 1326 schoolchildren took part in a questionnaire based, cross sectional survey. Parents of study participants were sent a postal questionnaire. Occurrence of body pain was ascertained using blank body manikins and, in children, psychosocial factors were assessed using the Strengths and Difficulties Questionnaire. Three child-parent pain relationships were examined: any child pain with any parental pain or with parental widespread pain; and child low back pain with parental low back pain. Results: The risk of child pain associated with parental reporting of pain was minor, and non-significant. Even when both parents reported widespread pain, the relative risk of pain in the child, after adjusting for age and psychosocial difficulties, was 1.2 (95% CI 0.5 to 3.2). Conclusions: Parental pain is not a risk for child pain. Pain behaviour is not learned. Rather, child pain is probably attributable to individual factors and the social environment.